The determination of measurement uncertainties for calibrations - Lenka Línková (Acta Montanistica Slovaca, 2005)
The paper describes some metrology problems and their applications in surveying. A result of the calibration an instrument or measuring tool should include also a value of uncertainty of the measurement. This term has been used in metrology only for several years so that the author gives a consideration to the philosophy of uncertainties and general principles of their determination. A practical example of uncertainty of the measurement calculation for the calibration of levelling rods for the precise levelling is also given.